Study of the Alternative Schools (ASs) under Education Guarantee Scheme (EGS) and its Contribution to SSA (Delhi) - Rekha, Chiter (JOURNAL OF INDIAN EDUCATION, 2014)
Education is the fundamental right of every child and in that direction Delhi Government is also determined to provide free and compulsory education to all children in the age-group 6-14 years. NCT of Delhi has shown good progress in the field of education and has obtained higher literacy rate than the national average in 2011 census, even so hundreds of children remain out-of-school and hence, the prospect of achieving UEE remains a distant dream. In this backdrop, the paper attempts to highlight the role and functions of Alternative Schools (ASs) under EGS for UEE for children in age-group 6-14 years in Delhi. This study involves various aspects related to quality dimensions of elementary education like infrastructure and basic facilities, teaching learning material and teaching learning process, perception of ASs functionaries’ towards ASs. The paper tries to ascertain whether the activities undertaken by the ASs are in accordance with the prescribed guidelines of SSA and RTE, and how far have they been successful? Thus the ultimate purpose of the study is to bring out the reality of the implementation of SSA with regard to Alternative Schools.